The role of procedural research in developing scientific research in Palestinian universities, Palestine Technical University, Kadoorie as a model - Shehadeh, Sonia AbdulFattah (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the role of procedural research in the development of scientific research in Palestinian universities. The Palestinian Technical University chose Khadouri as a model and examined the role of variables such as gender, scientific qualification, scientific rank, and years of experience in determining that role. To achieve the objectives of the study, the researcher developed a questionnaire consisting of (40) paragraphs distributed on two axes measuring the view of members of the academic body in the problem of study. The society consists of all the members of the academic faculty of the Technical University of Palestine Khadouri during the second semester of the academic year 2017-2018, with a total of (399) members and a sample of 240 members was chosen.The results showed that the role of procedural research in the development of scientific research in Palestinian universities was high. There were no statistically significant differences due to the variables of the study: type, scientific qualification, scientific rank and years of experience.In the light of the results, the researcher recommended the necessity of holding workshops related to procedural research mechanisms to define the procedural research mechanisms, and the inclusion of a special department within the scientific research department to support the research activities and the administration to provide its requirements and provide an environment conducive to its activities.
Keywords: Action Research; Scientific Research; Palestinian Universities; Palestine Technical University Khadouri